Planejamento urbano descentralizado - o planejamento de bairros na cidade de Santo André - Vale, Márcio Luiz (Universidade Federal de São Carlos, 2003)
This work research intends to rescue and to analyse the experience of the descentralized urban planning district planning, developed by town hall of Santo André in different moments of its history. We discussed about the concept principles of the descentralized urban planning of district, trying to estimate the possibility of a positive impact of this conception over the urban ambient. By the way, guidelines as the recue of the sociability, neighbourhood relationships and ecomonomic development that is distributed ina balanced way in the urban area are estimated from that concept, that is investigated and evaluated from the projects discussion made by the town hall of Santo André, mainly, about the programs Viva Cidade and Centros e Bairros. The analyse of the impacts of the pilot-projects of the program Centros e Bairros impacts, in Santo André, try to recognise the capacity of transformation of the urban area and the population relationship, especialy, the impacts over the descentralized economic development and more balanced than this proposals that take with them urban and social conceptions.
Keywords: Planejamento urbano; Planejamento de bairros; Unidades de vizinhança; Policentralidade; Santo André (SP); ENGENHARIAS